2023
DOI: 10.1038/s41598-023-28529-9
|View full text |Cite
|
Sign up to set email alerts
|

A spatial analysis of TB cases and abnormal X-rays detected through active case-finding in Karachi, Pakistan

Abstract: Tuberculosis (TB) is the leading cause of avoidable deaths from an infectious disease globally and a large of number of people who develop TB each year remain undiagnosed. Active case-finding has been recommended by the World Health Organization to bridge the case-detection gap for TB in high burden countries. However, concerns remain regarding their yield and cost-effectiveness. Data from mobile chest X-ray (CXR) supported active case-finding community camps conducted in Karachi, Pakistan from July 2018 to Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However a small proportion of 5% events accounted for 40% of the TB cases diagnosed. The authors concluded that a more targeted approach for ACF in high population metropolitan cities can increase the yield and cost-effectiveness of interventions [30].…”
Section: Discussionmentioning
confidence: 99%
“…However a small proportion of 5% events accounted for 40% of the TB cases diagnosed. The authors concluded that a more targeted approach for ACF in high population metropolitan cities can increase the yield and cost-effectiveness of interventions [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, a small proportion of 5% events accounted for 40% of the TB cases diagnosed. The authors concluded that a more targeted approach for ACF in high population metropolitan cities can increase the yield and cost-effectiveness of interventions [34].…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis remains a major international health problem and the leading cause of avoidable death despite advances in radiological diagnosis and antituberculous therapy as people often do not seek care due to poor knowledge of the disease, stigma, or health access barriers [ 1 , 2 , 3 ]. Extrapulmonary tuberculosis cannot be ruled out with a negative tuberculin test or clear chest X-ray.…”
Section: Introductionmentioning
confidence: 99%